2017
DOI: 10.29240/ef.v1i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Reading Anxiety Among Indonesian EFL Senior High School Students

Abstract: This study aims to investigate foreign language reading anxiety among Indonesian EFL Senior High School students. Thirty twostudents of grade eleven in a senior high school in Bandung were involved as the participants. This study employed a survey research design. The data was collected by two types of questionnaires. The first finding revealed that most of the students perceived anxiety in medium level (71,9% students admitted). The second finding found that there were two major potential factors of foreign l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 7 publications
5
29
0
Order By: Relevance
“…in her study also found that students' in junior high school had problems in reading. Meanwhile, Muhlis (2017) confirms that most of senior high school students perceived medium level of foreign language reading anxiety. As the result, most university students were not prepared for academic setting environment that insists them to be critical in reading the texts, therefore they adopt a superficial approach in reading academic materials.…”
Section: Introductionmentioning
confidence: 58%
“…in her study also found that students' in junior high school had problems in reading. Meanwhile, Muhlis (2017) confirms that most of senior high school students perceived medium level of foreign language reading anxiety. As the result, most university students were not prepared for academic setting environment that insists them to be critical in reading the texts, therefore they adopt a superficial approach in reading academic materials.…”
Section: Introductionmentioning
confidence: 58%
“…Several studies on FLRA have also been conducted in the Indonesian context from various education levels (Aisyah, 2017;Al Faruq, 2019;Mawardah et al, 2019;Muhlis, 2017;Sari, 2017). Both Aisyah (2017) and Muhlis (2017) found that their senior high school participants experienced a medium level of FLRA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anxiety experienced by learners in reading has been defined as Foreign Language Reading Anxiety (FLRA) (Saito et al, 1999). It is referred to as a feeling of worry and apprehension when learners attempt to read foreign language texts (Muhlis, 2017). When learners experience reading anxiety, they tend to have low self-perceived competence, feel hopeless, and overwhelmed (Aisyah, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations